The normal range of baseline tryptase should be 1 to 15 ng/mL and covers healthy individuals with HαT - Valent, Peter; Hoermann, Gregor; Bonadonna, Patrizia; Hartmann, Karin; Sperr, Wolfgang R.; Broesby-Olsen, Sigurd; Brockow, Knut; Niedoszytko, Marek; Hermine, Olivier; Chantran, Yannick; Butterfield, Joseph H.; Greiner, Georg; et al. (The journal of allergy and clinical immunology. In practice, 2023)
Physiological levels of basal serum tryptase vary among healthy individuals, depending on the numbers of mast cells, basal secretion rate, copy numbers of the TPSAB1 gene encoding alpha tryptase, and renal function. Recently, there has been a growing debate about the normal range of tryptase because individuals with the hereditary alpha tryptasemia (HαT) trait may or may not be symptomatic, and if symptomatic, uncertainty exists as to whether this trait directly causes clinical phenotypes or aggravates certain conditions. In fact, most HαT-positive cases are regarded as asymptomatic concerning mast cell activation. To address this point, experts of the European Competence Network on Mastocytosis (ECNM) and the American Initiative in Mast Cell Diseases met at the 2022 Annual ECNM meeting and discussed the physiological tryptase range. Based on this discussion, our faculty concluded that the normal serum tryptase range should be defined in asymptomatic controls, inclusive of individuals with HαT, and based on 2 SDs covering the 95% confidence interval. By applying this definition in a literature screen, the normal basal tryptase in asymptomatic controls (HαT-positive persons included) ranges between 1 and 15 ng/mL. This definition should avoid overinterpretation, unnecessary referrals, and unnecessary anxiety or anticipatory fear of illness in healthy individuals.